Elevated 24-hydroxycholesterol levels counteract okadaic acid-induced tau hyperphosphorylation and neuronal morphology impairment - Serena Giannelli; Francesca Eroli; Raúl Loera-Valencia; Valerio Leoni; Maria Latorre-Leal; Gabriella Testa; Erica Staurenghi; Barbara Sottero; Paola Gamba; Silvia Maioli; Gabriella Leonarduzzi (Neurobiology of Disease, 2025)
Multiple findings underline a link between altered brain cholesterol metabolism and Alzheimer's disease (AD) pathogenesis. Physiologically, excess brain cholesterol is mainly converted into 24-hydroxycholesterol (24-OHC) by the neuron-specific enzyme CYP46A1. Of note, we previously observed in autopsy specimens from human AD brains that 24-OHC and, in parallel, CYP46A1 expression decrease at advanced stages, suggesting a possible cause-effect between these reductions and AD progression. In the present study, we aimed to investigate whether maintaining high levels of 24-OHC, by its exogenous administration or CYP46A1 overexpression, can counteract tau hyperphosphorylation and accumulation of prefibrillar tau oligomers. To create an AD-like in vitro model exhibiting tauopathy, we utilized okadaic acid (OKA), a chemical compound that induces tau hyperphosphorylation. Our data show that in 24-OHC-treated primary neurons derived from wild type mice and in neurons from CYP46A1 overexpressing mice (CYP46Tg) elevated oxysterol levels effectively prevented tau hyperphosphorylation and oligomerization. Furthermore, the dendritic arborization decrease induced by OKA was prevented, maintaining the organization and stability of the neuronal cytoskeleton. While hypothesized underlying molecular mechanisms (GSK3β, CDK5, ERK1/2, and PP2A) seem not to be involved, the protective effect of 24-OHC remains evident. The data highlight the positive effects of 24-OHC and the need to prevent its reduction in the brain. This can be achieved either through the exogenous administration of 24-OHC using suitable technologies or by maintaining elevated levels and the activity of the enzyme CYP46A1. These therapeutic approaches could be useful to prevent or slow AD progression.